Effects of fixed and removable space maintainers on dental plaque and DMFT/dft values = Efecto de los mantenedores de espacio fijos y removibles en la placa dental y en los valores de los índices DMFT/dft - Tugce Gurcan, Aliye; Koruyucu, Mine; Kuru, Sinem; Sepet, Elif; Seymen, Figen (2021)
Purpose: Space maintainers are important for the health and placement of children's primary and permanent teeth. However, plaque and caries levels can be negatively affected when a dental appliance is in the mouth. This study aims to evaluate the oral health of pediatric patients that have space maintainers applied as a result of early tooth loss. Methods: This study included 100 systemically healthy patients between the ages of 4-15 years that were treated with space maintainers due to early loss of teeth. Decayed, missing, filled tooth index values and dental plaque status of the participants were recorded. Controls were performed in the 6th and 12th month. The index results were compared and evaluated statistically using ANOVA and paired-t-tests. Results: A total of 116 space maintainers, including 36 band and loops, 16 lingual arches, 21 palatal arches, 43 removable appliances, were evaluated in the study. Statistically significant differences were found between the pre-treatment and post-treatment index values (p<0.001). In the group of band and loops and removable space maintainers; the increases in DMFT/dft values of 6th month and 12th month according to initial DMFT/dft values were statistically significant (p<0.05). For plaque index, the increase in 12th month of all types of appliances were found statistically significant (p<0.001). The greatest increase in plaque index level was seen in the teeth of patients that had been treated with a lingual arch. Conclusions: Incompatible space maintainers can lead to caries, increased plaque accumulation, demineralized areas, and periodontal problems. The accumulation of plaque and difficulty of cleaning the teeth, especially in the fixed space maintainers, negatively affects the health of teeth. For this reason, good oral hygiene should be provided to patients and controls should be regularly performed.
Los mantenedores de espacio son importantes para la salud y la colocación de la dentición primaria y permanente de los niños. Sin embargo, los niveles de placa y caries pueden verse afectados negativamente cuando se coloca un aparato dental en la boca. Este estudio tiene como objetivo evaluar la salud bucal de pacientes pediátricos a los que se les aplicó mantenedores de espacio como resultado de la pérdida temprana de los dientes. Métodos: Este estudio incluyó a 100 pacientes sistémicamente sanos entre las edades de 4 a 15 años que fueron tratados con mantenedores de espacio debido a la pérdida temprana de dientes. Se anotaron los valores del índice de dientes cariados, faltantes y el estado de la placa dental. Los controles se realizaron en el 6 ° y 12 ° mes. Los resultados del índice se compararon y evaluaron estadísticamente mediante ANOVA y pruebas t pareadas. Resultados: Un total de 116 mantenedores de espacio, incluyendo 36 bandas y bucles, 16 arcos linguales, 21 arcos palatinos, 43 dispositivos removibles, fueron evaluados en el estudio. Se encontraron diferencias estadísticamente significativas entre los valores de los índices en el pretratamiento y postratamiento (p<0.001). En el grupo de bandas, bucles y mantenedores de espacio removibles los aumentos en los valores de DMFT/dft en el sexto mes y el 12º mes fueron estadísticamente significativos (p<0.05). Para el índice de placa, el aumento en el 12º mes de todos los tipos de aparatos se encontró estadísticamente significativo (p<0,001). El mayor aumento en el nivel del índice de placa se observó en los pacientes que habían sido tratados con un arco lingual. Conclusiones: los mantenedores de espacio pueden provocar caries, aumento de la acumulación de placa, áreas desmineralizadas y problemas periodontales. La acumulación de placa y la dificultad de limpiar los dientes, especialmente en los mantenedores de espacio fijos, afecta negativamente la saud dental...
En revista Odóvtos, vol. 23, no.2 (abril 2021)
Descripción basada en el contenido visto el 08 de noviembre, 2024
También disponible en formato HTML y EPUB